Validate the Precision of the RIPASA Grading System for the Diagnosis of Acute Appendicitis: A Cross-Sectional Study - Mansab Ali, Surrendar Dawani, Madiha Masood Khan, Salman Jafferi, Adeela Z Siddiqui, Rakesh Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the accuracy of the RIPASA (Raja Isteri Pengiran Anak Saleha Appendicitis) grading system for the diagnosis of acute appendicitis. Study design: A cross-sectional study Place and Duration: This study was conducted at Jinnah Postgraduate Medical Centre Karachi Pakistan from March 2020 to November 2021. Methodology: A total of 150 patients with clinical signs of acute appendicitis were studied. To determine the RIPASA score’s validity, testing was assessed for acute appendicitis. Patients with gynecological and urological disorders, appendicular lumps, were excluded from the study. The RIPASA Score chart was employed, and the findings of additional clinical studies corroborated the findings. Results: Among the 150 patients, 80 (53.3%) were males, and 70 (46.66%) were females. The participants’ average age was 22 ± 5.4 years. At a cut-off score of 7.5, the RIPASA scoring system exhibited good validation testing. The majority of the population (n=135, 90 %) was under the age of 40, with the minority (n=15, 10%) being over 40. The incidence of appendicitis increases dramatically in the second and third decades. There is no case below the age of ten and no case over the age of sixty years. Conclusion: For the diagnosis of AA, the RIPASA score is more sensitive and specific. This Scoring system is a valid and significant selective power in the diagnosis of appendicitis and in reducing unnecessary admissions and abdominal explorations, especially in the Asian race.